Traditional Market Revitalization in the Perspective of Public Policy Implementation (Study in Kuningan Regency Traditional Market) - Meylani, Memey; Suratno, Ade Inggit; Khumayah, Siti; Wulandari, Sri (Jurnal Polisci, 2024)
This study aims to determine the implementation of traditional market revitalization policies in Kuningan Regency. Revitalization of traditional markets is a form of public policy carried out by the government to improve the competitiveness of traditional markets amid the existence of modern markets as regulated in Kuningan Regency Regional Regulation Number 11 of 2011 concerning Arrangement, Development of Traditional Markets and Modern Stores. In addition, to find out the obstacles in implementing traditional market revitalization. The research method uses qualitative. Data collection techniques used are interviews, observation. Data analysis uses triangulation techniques. This research uses Merilee's theory. S. Grindle, that the successful implementation of public policy is influenced by two fundamental variables, namely the content of policy and the context of implementation. Based on the results of research on policy content, it shows that the desired changes from the policy have not been implemented optimally, the lack of communication carried out by program implementers, while from the context of implementing the traditional market revitalization policy is not optimal because there is a conflict of interest of the ruling regime. The obstacles in market revitalization are the lack of guidance on traditional market arrangements, and the lack of public awareness in the cleanliness of the market environment.